Thymus vulgaris Essential Oil and Its Biological Activity - Galovičová, Lucia; Borotová, Petra; Valková, Veronika; Vukovic, Nenad L.; Vukic, Milena; Štefániková, Jana; Ďúranová, Hana; Kowalczewski, Przemysław Łukasz; Čmiková, Natália; Kačániová, Miroslava (Plants (Basel), 2021)
Thymus vulgaris essential oil has potential good biological activity. The aim of the research was to evaluate the biological activity of the T. vulgaris essential oil from the Slovak company. The main components of T. vulgaris essential oil were thymol (48.1%), p-cymene (11.7%), 1,8-cineole (6.7), γ-terpinene (6.1%), and carvacrol (5.5%). The antioxidant activity was 85.2 ± 0.2%, which corresponds to 479.34 ± 1.1 TEAC. The antimicrobial activity was moderate or very strong with inhibition zones from 9.89 to 22.44 mm. The lowest values of MIC were determined against B. subtilis, E. faecalis, and S. aureus. In situ antifungal analysis on bread shows that the vapor phase of T. vulgaris essential oil can inhibit the growth of the microscopic filamentous fungi of the genus Penicillium. The antimicrobial activity against S. marcescens showed 46.78–87.80% inhibition at concentrations 62.5–500 µL/mL. The MALDI TOF MS analyses suggest changes in the protein profile of biofilm forming bacteria P. fluorescens and S. enteritidis after the fifth and the ninth day, respectively. Due to the properties of the T. vulgaris essential oil, it can be used in the food industry as a natural supplement to extend the shelf life of the foods.